Mangroves with therapeutic potential for human health : global distribution, ethnopharmacology, phytochemistry, and biopharmaceutical application - Sadeer, Nabeelah Bibi; Mahomoodally, Mohamad Fawzi (Academic Press, an imprint of Elsevier, 2022)
"Mangroves with Therapeutic Potential for Human Health: Global Distribution, Ethnopharmacology, Phytochemistry, and Biopharmaceutical Applications explores, for the first time in a book, the exciting potential of mangroves for therapeutic applications in medicine and pharmacology. This authoritative, illustrated and clearly written book pairs the fascinating biodiversity of mangroves with their promising pharmacological propensities. Providing a comprehensive and authoritative overview, the book explores the important aspects related to mangroves, including global distribution, medicinal values and pharmaceutical applications in one source. This book is a valuable resource for researchers, academics in the field of herbal medicine, pharmacology, pharmacognosy, medicinal chemistry, biochemistry, natural product chemistry, ethnopharmacology, biotechnology, marine biology, microbiology, as well as professionals in the pharmaceutical industries."--